Translating Standards into Practice with ELA Students - Kevin Murry; Socorro Herrera; Shabina Kavimandan; Della Perez (The Advocate, 2011)
Standards-based professional practices are increasingly a distinct focus of both teacher preparation and staff development. Yet, such standards are not always fully translated into rubrics for monitoring and assessment. This is no less the case as teachers build their capacities for English language acquiring (ELA) students. Recent trends indicate the widespread use ofthe CREDE, Standards for Effective Pedagogy and Learning (Doherty, Hillberg, Epaloose, andTharp, 2002) for this purpose. This article describes the history of, and rationales behind the translation of these standards into a more purposive Biography Driven Practices rubric for grade-level teachers of ELA students.